The Welfare Effects of Time Reallocation: Evidence from Daylight Saving Time - Joan Costa-Font; Sarah Flèche; Ricardo Pagan (Institute of Labor Economics (IZA), 2021)
Daylight Saving Time (DST) is currently implemented by more than seventy countries, yet we do not have a clear knowledge of how it affects individuals' welfare. Using a regression discontinuity design combined with a differences-in-differences approach, we find that the Spring DST causes a significant decline in life satisfaction. By inducing a reallocation of time, the transition into DST deteriorates sleep and increases time stress, which in turn affects physical and emotional health. After performing a simple cost-benefit analysis, we find evidence suggestive that ending DST would exert a positive effect on welfare, namely the wellbeing costs associated with DST exceed its benefits.
Keywords: I18; K2; I31; 330; health; wellbeing; Daylight Saving Time; sleep; time stress